2006
DOI: 10.1167/iovs.06-0231
|View full text |Cite
|
Sign up to set email alerts
|

Evoked Expression of the Glutamate Transporter GLT-1c in Retinal Ganglion Cells in Human Glaucoma and in a Rat Model

Abstract: The induction of GLT-1c expression by retinal ganglion cells supports the notion that an anomaly or anomalies in glutamate homeostasis may be evident in glaucoma and that such anomalies selectively influence retinal ganglion cells. By analogy to in vitro experiments in which elevated glutamate levels induce expression of glutamate transporters, the authors hypothesize that expression of GLT-1c may represent an attempt by retinal ganglion cells to protect themselves against elevated levels of glutamate. Such an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…120 Glaucoma Expression of the splice variant EAAT2c/GLT1c is induced in retinal ganglion cells in human glaucoma samples and in rat retina exposed to increased intraocular pressure. 121 In contrast, GLT1c is restricted to photoreceptors in the normal retina.…”
Section: Brain Injurymentioning
confidence: 99%
“…120 Glaucoma Expression of the splice variant EAAT2c/GLT1c is induced in retinal ganglion cells in human glaucoma samples and in rat retina exposed to increased intraocular pressure. 121 In contrast, GLT1c is restricted to photoreceptors in the normal retina.…”
Section: Brain Injurymentioning
confidence: 99%
“…These results suggest that integrity of GLT-1 may be a prerequisite for the maintenance of glutamate homeostasis in the retina undergoing glaucoma [67]. Sullivan et al (2006) [68] reported the expressional changes of the splice variant of GLT-1 (GLT-1c) in the glaucoma eyes. In normal eyes of humans and rats, GLT-1c is expressed only in photoreceptors.…”
Section: B Glt-1mentioning
confidence: 85%
“…GLT-1, the main neuronal glutamate transporter in the retinal neurons, is reported to be downregulated in glaucomatous eyes in rats [58,66] and mice [57]. By contrast, Park et al [58] reported that the expression of GLT-1 was expressed in cone photoreceptors and the level of expression in some cone bipolar cells was significantly increased in in vivo glaucoma model.…”
Section: B Glt-1mentioning
confidence: 99%
“…Recently, it has been suggested that several IOP-independent factors such as circulatory disorders, autoimmunity, and glutamate toxicity are associated with the progression of glaucomatous optic neuropathy. [18][19][20] Further studies will be required to elucidate the risk factors related to fi xation loss during the chronic postsurgery phase in eyes with advanced glaucoma.…”
Section: Discussionmentioning
confidence: 99%